Ethnic Dynamics on the Musi River: A Historical Review and Its Role as a Cultural Connecting Route - Anggun Dwi Dyaloka (Swarnadwipa, 2026)
The Musi River, a major artery in South Sumatra, has served as a cultural link between ethnic groups from prehistoric times to the contemporary era. This study explores ethnic dynamics along the river, focusing on its role in connecting the cultures that pass through it. Using a qualitative case study approach, the findings demonstrate that the river facilitates not only trade but also the exchange of values, rituals, and ethnic identities. Historical and ethnographic analyses reveal how the Musi River has fostered multiethnic harmony amidst modern challenges such as urbanization.